Studying the Immunogenic Properties of Plague Microbe Capsule Antigen F1 Conjugated with Nanoparticles of Colloid Gold and Silver - M. N. Kireev; T. A. Polunina; N. P. Guseva; N. A. Podboronova; Ya. M. Krasnov; T. M. Taranenko (Проблемы особо опасных инфекций, 2008)
Influence of nanoparticles of colloid gold (CG) and silver (CS) on immunobiological properties of antigens and possibility of their application as adjuvants for antibody formation stimulation were studied. It was shown that F1 capsule antigen of plague microbe conjugated with nanoparticles of CG and CS possesses more strongly expressed immunogenic properties than original F1 antigen independently of the way of injection. Gold and silver sols with antigens are stable, capable to stimulate specific antibody generation subject to less antigen burden, comfortable for use, do not cause general and local reactions. All these facts give the opportunity to use them in immunologic practice as adjuvants when engineering immunobiological preparations.